2009
DOI: 10.1177/0363546509334591
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Glenohumeral Instability in Collegiate Athletics

Abstract: Glenohumeral instability is a relatively common injury sustained by collegiate athletes. More injuries occurred during competition and among male athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
237
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(255 citation statements)
references
References 12 publications
10
237
2
4
Order By: Relevance
“…The highest risk group was young (< 20 years), male patients with an incidence density ratio of 98 per 100000 person-years. Other studies have also shown that young athletes and those that participate in high-energy contact sports are most likely to develop glenohumeral instability following an initial traumatic dislocation [9,10] . Epileptic patients present as a challenging subgroup due to a tendency to develop large bipolar lesions, especially if their condition is poorly controlled [11,12] .…”
Section: Epidemiologymentioning
confidence: 99%
“…The highest risk group was young (< 20 years), male patients with an incidence density ratio of 98 per 100000 person-years. Other studies have also shown that young athletes and those that participate in high-energy contact sports are most likely to develop glenohumeral instability following an initial traumatic dislocation [9,10] . Epileptic patients present as a challenging subgroup due to a tendency to develop large bipolar lesions, especially if their condition is poorly controlled [11,12] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Non-surgical shoulder immobilization technique for 4 weeks followed by rehabilitation [14] Bankart lesion repair by arthroscopy [10] Control Procedure:…”
Section: Us 3 Yearsmentioning
confidence: 99%
“…With a peak of bimodal incidence, the 15 -29 age group shows 46.8% of shoulder dislocations, with another peak of incidence in the group of 61 -80 age related to low-energy trauma [7] [8]. A review of the National Collegiate Athletic Association (NCAA) analyzed an injury surveillance system during the years 1989 to 2004 reporting 2080 glenohumeral instabilities in various sports and equating the rate of injuries in 0.12/1000 exposed athletes, most in sports such as football, wrestling and hockey [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…A nterior shoulder dislocations are common injuries, 1 and young male athletes who participate in contact sports have particularly high rates, approaching 90%, of recurrent instability. 2,3 The Bankart lesion, in which the anteroinferior glenoid labrum is detached from the glenoid, is the critical lesion present in more than 90% of cases, 4,5 although other co-pathology must be identified carefully and addressed appropriately for successful treatment.…”
mentioning
confidence: 99%